Editor's Foreword - Waicus, Sarah (Trinity Student Medical Journal, 2025)
The latest edition of the Trinity Student Medical Journal explores the transformative role of artificial intelligence in modern medicine, showcasing its growing impact across clinical care, education, and global health. This volume features a wide range of articles, from AI-assisted neonatal care in low-resource settings to the integration of AI into general practice, highlighting both its potential and the ethical challenges it raises. Alongside this focus, the issue includes diverse contributions spanning stroke treatments, COVID-19 sequelae, appendicitis management, and the evolving fentanyl crisis. Thoughtful pieces on medical ethics and emerging diagnostics round out this dynamic, forward-looking edition. In keeping with the theme of this edition, let us remember the core principle of the Hippocratic Oath: primum non nocere. This guiding tenet serves as a reminder to embrace the integration of artificial intelligence in healthcare, while always keeping our primary duty—to do no harm—at the forefront of innovation.